المعايير والركائز الأساسية لتحقيق جودة المراجعة الداخلية في الشركات الجزائرية - كينة, عبد الحفيظ; جلاب, محمد (جامعة الوادي - University of Eloued, 2023)
تبين هذه الدراسة التطور التاريخي والقانوني لمهنة المراجعة الداخلية في الجزائر وتبرز واقعها على مستوى الشركات الإقتصادية، وتحدد أهم العناصر التي تأثر في جودة المراجعة الداخلية ومعاييرها ومؤشرات قياسها، ومن خلال هذه الدراسة أيضا حاولنا إظهار أن التزام الشركات بالمعايير الدولية للمراجعة الداخلية يعتبر من المحددات المحورية لتحقيق جودة المراجعة الداخلية، وأن هذه الأخيرة لا يمكنها أن تقوم بأدوارها بفاعلية وتسهم في تحقيق أهدافها وتعزيز عمليات حوكمة الشركات وإدارة المخاطر والرقابة، إلا إذا كانت تتم وفقا للقواعد والمعايير المتعارف عليها دوليا. This study shows the historical and legaldevelopment of the internal audit profession in Algeria and highlights its reality at the level of economiccompanies, it identifies the most important elementsthat affect the quality of internalauditing, its standards, and itsmeasurementindicators. Throughthisstudy, wealsotried to show thatcompaniescommitment to international standards of internalauditingis one of the pivotal determinants of achieving the quality of internalauditing, and that the audit cannotplayitsroleseffectively and contribute to achievingits objectives and strengthening the processes of corporategovernance, risk management and control, unlessitiscarried out in accordance withinternationallyrecognizedrules and standards.
Standards and Basic Pillars to Achieve The Quality of Internal Auditing in Algerian Companies
مقال
Keywords: جودة المراجعة الداخلية ; المعايير الدولية للمراجعة الداخلية; Internal Audit Quality, International Standards of Internal Auditing.